Justice Systems Processing of Child Abuse and Neglect Cases in a Local Jurisdiction (County) in the United States, 1993-1994 - Wells, Susan J. ([Verlag nicht ermittelbar], 2000)
The purpose of this study was to provide a comprehensive, case-level examination of the full spectrum of case processing of serious child abuse and neglect cases as they flowed through the justice process, from initial receipt of a report to final disposition in the criminal and/or civil court. This was accomplished by in-depth, detailed tracking, from a single jurisdiction, of both prospective and retrospective samples of serious child abuse cases reported to child protective services and law enforcement agencies. The four agencies that participated directly by providing case samples and case files for tracking were: (1) Child Protective Services (CPS), (2) the sheriff's office, (3) Dependency Court Legal Services (DCLS), and (4) the county prosecutor's office. Each case was abstracted at the point of sampling and then tracked throughout the other participating agencies. Data were collected over a nine-month period. Part 1, Maltreatment Abstract, Person Roster, and CPS Abstract Data, contains three types of data. First, information is provided on each maltreatment incident committed by each perpetrator, background of the perpetrator and the victim, and characteristics of the incident. The data continue with a roster of persons, which covers the relationships among the individuals in the case and whether any of these individuals were living together at the time of the maltreatment. Data from the CPS abstract include which source brought the case to the attention of Protective Services, the dates, priority, and investigation level of the report, if any prior allegations of maltreatment had occurred that involved either the same victims and/or perpetrators and, if so, information on those reports, and the perpetrator's response to the incident and level of cooperation with the investigation. For each victim, information is given on medical findings, if applicable, whether photographs were taken, whether a guardian was appointed, whether the victim was assigned an interim placement, and the CPS disposition of the case. Part 1 concludes with information on interviews with the victim, where the case was referred, the assessment of risk in the case, and whether the victim was placed in foster care. Part 2, Dependency Court Abstract Data, provides information on the case, the reason the case was closed, and the outcome as determined by the court. Part 3, Juvenile Court Schedule of Hearings Data, focuses on the schedule of hearings, such as who was present and if they were represented by an attorney, whether the hearing took place, and, if not, the reason for delay. Part 4, Law Enforcement Abstract Data, contains dates of incidents, reports, and arrests, details of the case, and how the case was handled. Part 5, State Attorney's Office Abstract Data, offers data on the case closing, charges, and sentencing, as well as information on the type of defense attorney representing the perpetrator, if a juvenile, how the defendant was referred to adult court, whether the state attorney filed cases on other perpetrators in the case, whether the victim was interviewed by the prosecutor prior to filing, and whether the victim was deposed by the state attorney after the case was filed. Part 6, Criminal Court Schedule of Hearings Data, contains information on date of arrest, filing, and court hearing, whether a public defender was assigned, number of hearings, type of hearing, and coded remarks about the hearing. Part 7, State Attorney Addendum Data, provides "no-file" data from the State Attorney Questionnaire Addendum, including if the no-file was a warrant or arrest, date of the no-file, and reason for the no-file.